Vertically Aligned Nanostructured Topographies for Human Neural Stem Cell Differentiation and Neuronal Cell Interrogation. Issue 9 (23rd June 2021) - Lestrell, Esther; O'Brien, Carmel M.; Elnathan, Roey; Voelcker, Nicolas H.
Abstract: Neurodegenerative disorders are a widespread global health concern caused by aging, disease, and trauma, for which there are limited treatment options. Stem cell therapies, tissue engineering, and nanobiotechnologies offer hope for improved therapeutic delivery approaches, as well as tissue repair and regenerative medicine interventions. The complexity of the human brain, coupled with its limited availability for research, makes human neural lineage cells and their precursor stem cells integral to the further understanding of brain functions in health, development, and disease. Engineered nanomaterials provide highly specialized microenvironments, enabling precise interrogation of the impact of external and spatial stimuli on human neural cells in vitro, greatly advancing the knowledge of human neural function. Interacting with neural cells at the nanoscale, vertically aligned nanostructured (VA‐NS) arrays can influence cell fate and aid in more efficient cell reprogramming, and lend themselves to the development of highly targeted, sensitive signal transducer platforms suitable for in vivo monitoring of neural cell health and activity. This perspective highlights the current state of stem cell nanoneurobiology, specifically focusing on interdisciplinary advances made by VA‐NS arrays to manipulate human neural stem cells in translatable research applications. Current challenges and identify are discussed underexplored and emerging future research areas. Abstract : Surfaces featuring vertically aligned nanostructures (VA‐NSs) used as innovative cell‐culture substrates enable precise control of cell behavior. VA‐NS arrays fabricated as uniform or stochastic ridges, tubes, and needles, capitalize on optical, electrical, and chemical material properties at the nanoscale. This perspective highlights stem cell nano‐neurobiology, and advances made by VA‐NS arrays to manipulate human neural stem cells in translational research applications.